Juegos que inciden en la motivación y el aprendizaje en la educación emprendedora, caso: Cafet (2019)
This work seeks to establish the contribution of the implementation of Cafet, a card game based on the coffee industry and framed in the category of game based learning (GBL), on the teaching of entrepreneurship in universities in Central and South America, taking as a reference the evaluation and impact assessment in 12 institutions in the region. The methodology was implemented based on an analysis of the Cronbach's Alpha coefficient and the results on the students' perception of the constructs Challenge and Clarity, Immersion and Purpose, and Control and Interest associated with increasing motivation for learning. We found a positive impact of the game Cafet in the motivation and perception of learning of students around the enterprise, it was also found that the teachings and dynamics of Cafet are supported from the analysis of a group of experts as an alternative to traditional education.